2001
DOI: 10.1046/j.1440-6047.2001.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐emergence of iodine deficiency in Australia

Abstract: Iodine is an essential nutrient for human growth and development. The thyroid gland is dependent upon iodine for production of thyroid hormone. It is a common perception that iodine deficiency is not a major public health concern in mainland Australia, with sporadic studies carried out about a decade ago showing average urinary iodine excretion levels of around 200 microg/day. Recent evidence, however, has shown that the consumption of iodine is declining in Australia. A similar situation has occurred in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 19 publications
(26 reference statements)
11
86
0
Order By: Relevance
“…Children in Western Australia and Queensland were found to be iodine replete by comparison. The results from NSW and Victoria were very similar to those previously reported [27][28][29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Children in Western Australia and Queensland were found to be iodine replete by comparison. The results from NSW and Victoria were very similar to those previously reported [27][28][29].…”
Section: Discussionsupporting
confidence: 90%
“…72% of a sample of pregnant women in Western Sydney were iodine deficient, with 32% suffering from moderate deficiency [30]. The MUIC of 81 μg/L was similar to the level found in a pregnant population in Sydney approximately 10 years prior indicating that the situation had not improved despite publicity in the medical and lay press about iodine deficiency [27]. Similar reports of iodine deficiency from Victoria and Tasmania indicate the degree of iodine deficiency in pregnant women (52 μg/L) was even worse than in NSW [11,18].…”
Section: Discussionmentioning
confidence: 72%
“…These results support those of Thomson et al (1997), who found mild IDD in New Zealand adults. A recent study in Sydney, Australia also found mild IDD as determined by casual urine samples in school-aged children (Li et al, 2001). A prevalence of thyroid volume > ULN between 5 and 20% of children is suggested by WHO=ICCIDD=UNICEF to be indicative of mild IDD (WHO et al, 1994).…”
Section: Discussionmentioning
confidence: 97%
“…The mean amount of iodine provided by MPD in 2007 was somewhat greater than this (56-93 mg iodine); nevertheless, the proportion contributed to total iodine intake from dairy foods is expected to have fallen due to the additional intake from fortified bread. Also, the iodine concentration of milk is variable (18) and may be influenced by production methods.…”
Section: Dairy Food Intake Patternmentioning
confidence: 99%